The number of love eaudiobook - White, Roseanna M. (Codebreakers, 2019)
The Toughest Puzzle She'll Have to Solve Might Be the Wishes of Her Own Heart Three years into the Great War, England's greatest asset is their intelligence network—field agents risking their lives to gather information, and codebreakers able to crack German telegrams for hints of the enemy's plans. Margot De Wilde thrives in the environment of the secretive Room 40, where she spends her days deciphering intercepted messages. But when her world is turned upside down by an unexpected loss, she discovers for the first time in her life that numbers aren't enough. Drake Elton returns wounded from the field, followed by an enemy who just won't give up. He's smitten quickly by the quick and brainy Margot, but soon the dangers of the war draw ever closer. Margot and Drake will have to team up to save themselves from the very secrets that brought them together. "Acclaimed author White begins her newest series, The Codebreakers, with an exciting tale steeped in the historical intelligence game of the Great War. The Number of Love is captivating and features White's signature use of energetic plots and high-octane drama."—Booklist